Bacterial biofilm dependent catheter associated urinary tract infections: Characterization, antibiotic resistance pattern and risk factors. Issue 1 (1st January 2021) - Ramadan, Reham; Omar, Nesrene; Dawaba, Mohamed; Moemen, Dalia
ABSTRACT: Biofilms cause recurrent and resistant device-related infections. We aimed to detect the prevalence of biofilm-dependent catheter-associated urinary tract infections (CAUTI) among catheterized patients, identify bacterial pathogens, antibiotic resistance pattern and risk factors associated with biofilm production. Adult and pediatric patients admitted to Mansoura University Urology and Nephrology Center and fulfilling the criteria of CAUTI were enrolled in this study. urine sample and a part of urinary catheter were collected for microbiological testing and assessment of biofilm formation using tube method (TM) and scanning electron microscope (SEM). The prevalence of biofilm-dependent CAUTI was 82.85%, in which Klebsiella pneuomoniae had the highest biofilm-forming potential. Biofilm producers uropathogens are more resistant to antibiotics. Extremes of age and prolonged duration of catheterization were significantly associated with biofilm formation. TM showed good correlation with SEM regarding degree of biofilm production, sensitivity (100%) and specificity (100%). Prevalence of biofilm-dependent CAUTI was high. Minimizing the duration of catheterization and usage of silicone catheter are recommended. Using carbapenems in treatment of biofilm-dependent CAUTI should be considered. TM can be implemented for biofilm detection as it is cheap, rapid, easy and showed good correlation with SEM.